2021
DOI: 10.1073/pnas.2018840118
|View full text |Cite
|
Sign up to set email alerts
|

Violet light suppresses lens-induced myopia via neuropsin (OPN5) in mice

Abstract: Myopia has become a major public health concern, particularly across much of Asia. It has been shown in multiple studies that outdoor activity has a protective effect on myopia. Recent reports have shown that short-wavelength visible violet light is the component of sunlight that appears to play an important role in preventing myopia progression in mice, chicks, and humans. The mechanism underlying this effect has not been understood. Here, we show that violet light prevents lens defocus–induced myopia in mice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
44
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 70 publications
(55 citation statements)
references
References 68 publications
1
44
0
Order By: Relevance
“…In addition to melanopsin, another atypical photopigment, neuropsin (Opn5), is expressed in the retina of vertebrates ranging from zebrafish to humans (Davies et al., 2015; Tarttelin et al., 2003). Functionally characterized as a UVA (380 nm)‐sensitive opsin in humans and mice (Kojima et al., 2011), retinal neuropsin signaling has been implicated in autonomous entrainment of the retinal clock (Buhr et al., 2015), behavioral entrainment to scotopic violet light (Ota et al., 2018), regression of the hyaloid vessels in the eye (Nguyen et al., 2019), and is required for short‐wavelength‐mediated suppression of myopia development in mice (Jiang et al., 2021). Though neuropsin signaling and function appear important in diverse aspects of ocular physiology and health, little is known beyond its expression in a subset of RGCs (Buhr et al., 2015; Jiang et al., 2021; Nguyen et al., 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to melanopsin, another atypical photopigment, neuropsin (Opn5), is expressed in the retina of vertebrates ranging from zebrafish to humans (Davies et al., 2015; Tarttelin et al., 2003). Functionally characterized as a UVA (380 nm)‐sensitive opsin in humans and mice (Kojima et al., 2011), retinal neuropsin signaling has been implicated in autonomous entrainment of the retinal clock (Buhr et al., 2015), behavioral entrainment to scotopic violet light (Ota et al., 2018), regression of the hyaloid vessels in the eye (Nguyen et al., 2019), and is required for short‐wavelength‐mediated suppression of myopia development in mice (Jiang et al., 2021). Though neuropsin signaling and function appear important in diverse aspects of ocular physiology and health, little is known beyond its expression in a subset of RGCs (Buhr et al., 2015; Jiang et al., 2021; Nguyen et al., 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Functionally characterized as a UVA (380 nm)‐sensitive opsin in humans and mice (Kojima et al., 2011), retinal neuropsin signaling has been implicated in autonomous entrainment of the retinal clock (Buhr et al., 2015), behavioral entrainment to scotopic violet light (Ota et al., 2018), regression of the hyaloid vessels in the eye (Nguyen et al., 2019), and is required for short‐wavelength‐mediated suppression of myopia development in mice (Jiang et al., 2021). Though neuropsin signaling and function appear important in diverse aspects of ocular physiology and health, little is known beyond its expression in a subset of RGCs (Buhr et al., 2015; Jiang et al., 2021; Nguyen et al., 2019). Our understanding of light's influence on physiology and health has stemmed in large part from the evaluation of the unique projections and characteristics of M1–M6 ipRGCs.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, in a previous study, visible violet light was found to be effective in preventing the onset of myopia in humans [ 35 ]. Furthermore, the molecular mechanism of this effect is being elucidated, and it was clarified that violet light is received by OPN5 (neuropsin), a photoreceptor expressed in retinal ganglion cells in the inner layer of the mouse retina that is involved in local retinal circadian rhythms, intraocular vascular development, and regulation of deep body temperature, thereby suppressing myopia progression by maintaining choroidal thickness [ 36 ]. Therefore, the time of day of exercise may be important for the prevention of visual impairment.…”
Section: Discussionmentioning
confidence: 99%
“…With the evolvement of light-emitting diode (LED) technology, the spectral composition of artificial lighting has changed significantly, with an increase in short wavelength (e.g., blue) and decrease in long wavelength (e.g., red) components ( Behar-Cohen et al, 2011 ). Studies have also shown that different light spectra, e.g., violet ( Jiang et al, 2021a ; Mori et al, 2021 ) and red light ( Hung et al, 2018 ; Jiang et al, 2021b ; Smith et al, 2015 ) can affect myopia development in humans and animals. Given the importance of the light spectrum to the occurrence and development of myopia, the compositional transformation of artificial light spectra in recent years may be related to the increase in myopia incidence.…”
mentioning
confidence: 99%
“…In addition, spending more than 3 h outdoors every day can significantly reduce the incidence rate of myopia in school children ( French et al, 2013 ; Rose et al, 2008 ), with sunlight likely playing a very important role. Short wavelength blue light ( Rucker et al, 2015 , 2018 ) and violet light ( Jiang et al, 2021a ; Mori et al, 2021 ; Torii et al, 2017 ) are also implicated in the inhibition of myopia. The relationship between these different research results and our findings is still unclear and needs to be further studied.…”
mentioning
confidence: 99%